TINDAK TUTUR ILOKUSI KOMISIF DALAM DIALOG FILM â€œSOPHIE SCHOLL - DIE LETZTEN TAGEâ€ KARYA MARC ROTHEMUND - AYU DARUSFANTI, DINI (UNIVERSITAS NEGERI SURABAYA, 2016)
Certainly interesting when reviewing how the illocutionary speech commissive figures based on the film that has been declassified transcripts of interrogations. The characters in the film do the interaction in the form of communication with the other figures. Communication is contained in a dialog. Leaders of the dialogue in the film is used to express an intent and purpose are accompanied by expressions and gestures. By using a knife commissive illocutionary speech act theory by John R. Searle, this study seeks to dissect the great veil. By using qualitative descriptive method, this research focuses on speech illocutionary commissive the characters in the dialogue the film